Congenic Mapping of the Type 1 Diabetes Locus, Idd3, to a 780-kb Region of Mouse Chromosome 3: Identification of a Candidate Segment of Ancestral DNA by Haplotype Mapping - Lyons, Paul A.; Armitage, Nicola; Argentina, Fabio; Denny, Paul; Hill, Natasha J.; Lord, Christopher J.; Wilusz, Mary Beth; Peterson, Laurence B.; Wicker, Linda S.; Todd, John A.

(untitled) (Genome Research, 2000)
Type 1 diabetes in the nonobese diabetic (NOD) mouse arises as a consequence of T cell-mediated destruction of the insulin-producing β cells of the pancreas. Although little is known of the events that initiate and subsequently drive β-cell destruction it is clear that the entire process is under complex genetic control. At present 19 loci have been mapped that influence the development of diabetes either at the level of initiation of insulitis or at the level of progression from insulitis to overt diabetes, or both. Previously, we have mapped one of these loci, Idd3, to a 0.35-cM interval on proximal mouse chromosome 3. In the present study we have narrowed the map position of this locus to an interval of 0.15 cM by a combination of novel congenic strains and an ancestral haplotype analysis approach. We have constructed a physical contig in bacterial artificial chromosome (BAC) clones across the minimal interval. Restriction mapping of the BAC contig placed the maximum size of the Idd3 interval at 780 kb between the markers D3Nds36 and D3Nds76. To refine further the Idd3 interval we developed a series of novel single nucleotide polymorphisms (SNPs) and carried out haplotype analysis on DNA from mouse strains known to carry either Idd3susceptibility or protective alleles. This haplotype analysis identified a 145-kb segment of ancestral DNA between the microsatellite marker D3Nds6 and the SNP 81.3. One haplotype of this ancestral segment of DNA is found in mouse strains carrying anIdd3 susceptibility allele and another is found in mouse strains carrying an Idd3 protective allelle. Within the 780-kb congenically defined interval this 145-kb segment represents the most likely location for Idd3. The Il2 gene, which encodes the cytokine interleukin 2 (IL2), maps to this interval and is a strong candidate for Idd3. To investigate whether sequence variation exists in the promoter region of the Il2 gene, which might alter its expression, we sequenced the promoter region of theIl2 gene from mouse strains carrying either an Idd3susceptibility or resistance allele. Two sequence variants were identified, neither of which fell in known regulatory elements within the Il2 promoter. In agreement with this observation steady-state Il2 mRNA levels showed no variation between susceptible and resistant mouse strains. These data suggest that the profound protection from diabetes seen in congenic mice carrying anIdd3 protective allele is unlikely to be due to differences in the level of expression of the Il2 gene. Instead, all of the current data support our hypothesis that Idd3 corresponds to amino acid variation at the amino terminus of Il2.[Sequence data reported in this paper have been deposited in GenBank and assigned the following accession numbers: AF19594, AF19595, and AF19596.]